2014
DOI: 10.4244/eijv9i11a220
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical complications of everolimus-eluting stents associated with adverse events: an intravascular ultrasound study

Abstract: We found EES mechanical complications, often followed by longitudinal deformation or fracture leading to excessive neointimal hyperplasia, in-stent restenosis, and repeat revascularisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…5 In addition, aggressive guide catheter manipulation, use of imaging devices including IVUS or optical coherence tomography, and multiple ballooning have been suggested as factors associated with LSD occurrence. 2,3,9,19,20 Our subgroup analysis also showed that any use of secondary devices was the single most important independent factor predicting QCA-based LSD, regardless of the lesion or stent factors. If the proximal portion of the stent is not completely apposed to the vessel wall, frequent use of secondary devices may increase the chance of contact with unopposed struts especially when wire bias exists resulting in the occurrence of LSD.…”
Section: Procedural Insights On the Mechanism Of Lsdmentioning
confidence: 76%
See 1 more Smart Citation
“…5 In addition, aggressive guide catheter manipulation, use of imaging devices including IVUS or optical coherence tomography, and multiple ballooning have been suggested as factors associated with LSD occurrence. 2,3,9,19,20 Our subgroup analysis also showed that any use of secondary devices was the single most important independent factor predicting QCA-based LSD, regardless of the lesion or stent factors. If the proximal portion of the stent is not completely apposed to the vessel wall, frequent use of secondary devices may increase the chance of contact with unopposed struts especially when wire bias exists resulting in the occurrence of LSD.…”
Section: Procedural Insights On the Mechanism Of Lsdmentioning
confidence: 76%
“…18 In line with these results, an IVUS analysis also reported that the incidence of LSD was similar among various types of second-generation DES. 19 These findings suggest that factors other than the stent platform itself, such as lesion or procedural factors, may have had a greater impact on the occurrence of QCA-based LSD.…”
Section: Rhee Et Al Risk Factors Of Longitudinal Stent Deformationmentioning
confidence: 79%
“…partial or complete stent fracture, strut fracture with overlapping stent fragments, and longitudinal deformation) have been associated with excessive neo-intimal hyperplasia, ISR and repeat revascularisation. 30 Sonoda et al 31 observed a correlation between BMS and SES MSA and long term development of ISR. Fujii et al 32 found stent under expansion (MSA < 5.0 mm 2 ) to be associated with ISR after SES implantation.…”
Section: Ivus For Bms and Des Implantationmentioning
confidence: 98%
“…The most common categories are longitudinal stent deformation, stent fracture, stent under expansion and stent recoil [18]. The MSF rate reported that from 136 patients undergoing stent implantation, 17 patients (12.5%) endure mechanical stent failure [19]. From 17 patients, 16 having focal and 1 having in stent restenosis (ISR) [19].…”
Section: Failure Of Stentmentioning
confidence: 99%
“…There are three types of diffuse ISR, which are confined to stent margin, beyond stent margin, and total occlusion or have a flow rate 0 [21]. Complete stent fracture occur in one patient (5.9%), partial stent fracture endure by 3 patients (17.6%) while 13 (76.5%) more experienced longitudinal deformation and stent's strut fracture [19].…”
Section: Failure Of Stentmentioning
confidence: 99%